The Potential Biomarkers and Immunological Effects of Tumor-Derived Exosomes in Lung Cancer - Alipoor, Shamila D.; Mortaz, Esmaeil; Varahram, Mohammad; Movassaghi, Mehrnaz; Kraneveld, Aletta D.; Garssen, Johan; Adcock, Ian M. (Frontiers in Immunology, 2018)
Lung cancer remains the leading cause of cancer-related deaths worldwide. Despite considerable achievements in lung cancer diagnosis and treatment, the global control of the disease remains problematic. In this respect, greater understanding of the disease pathology is crucially needed for earlier diagnosis and more successful treatment to be achieved. Exosomes are nano-sized particles secreted from most cells, which allow cross talk between cells and their surrounding environment via transferring their cargo. Tumor cells, just like normal cells, also secret exosomes that are termed tumor-derived exosome or TEX. TEXs have gained attention for their immuno-modulatory activities, which strongly affect the tumor microenvironment and antitumor immune responses. The immunological activity of TEX influences both the innate and adaptive immune systems including NK cell activity and regulatory T-cell maturation as well as numerous anti-inflammatory responses. In the context of lung cancer, TEXs have been studied in order to better understand the mechanisms underlying tumor metastasis and progression. As such, TEX have the potential to act both as a biomarker for lung cancer diagnosis as well as the response to therapy.